The influence of work discipline and work climate on teacher performance in public elementary schools in Tanah Merah district, Indragiri Hilir regency - Effendy; Sumarno; Erni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to analyze the influence of work discipline and work climate on the performance of state elementary school teachers in Tanah Merah District, Indragiri Hilir Regency. The type of research carried out was descriptive quantitative. The choice of descriptive quantitative in this research is the ex post facto method with correlational research techniques, namely a correlation study that aims to test hypotheses. The population and sample in this research were state elementary schools in Tanah Merah District, Indragiri Hilir Regency, totaling 91 people. The data collection technique used to obtain data is by administering a questionnaire. The questionnaire is closed; an answer is provided for each question item and is measured using a Likert scale. The data analysis technique used in this research is quantitative descriptive analysis. Hypothesis testing in this research was conducted after testing classical assumptions using SPSS Version 24.0 software. The testing stages are carried out using analysis: (a) descriptive statistics, (b) inferential statistics, and (c) multiple linear regression analysis. Based on the results of data analysis and hypothesis testing in this research, the following conclusions can be drawn: (a) first, there is an influence of work discipline and work climate on teacher performance; (b) second, there is an influence of work discipline on teacher performance; and (c) there is an influence of work climate on the performance of state elementary school teachers in Tanah Merah District, Indragiri Hilir Regency.